UHPLC–MS/MS determination and pharmacokinetic study of plantamajoside in rat plasma after oral administration of single plantamajoside and Plantago asiatica extract. (13th December 2016) - Bai, Lizhi; Han, Li; Lu, Xiaoguang; Kang, Xin; Fan, Zhiwei; Xing, Rong; Zhou, Dangxia
Abstract: A sensitive and reliable ultra‐high performance liquid chromatography coupled with tandem quadrupole mass spectrometry (UHPLC–MS/MS) method was developed for quantitation of plantamajoside in rat plasma. First, this study compared the pharmacokinetic properties of plantamajoside after oral administration of Plantago asiatica extract and pure plantamajoside in rat plasma with approximately the same dosage of 8.98 mg/kg. Second, chromatographic separation was performed on an Acquity HSS C18 column (50 × 2.1 mm, p.d.1.7 μm) with isocratic elution using methanol–water (80:20, v /v) as mobile phase at a flow rate of 0.25 mL/min. The calibration curves were linear over the range of 0.1–100 ng/mL for plantamajoside. At different time points (0, 0.083, 0.167, 0.25, 0.5, 0.75, 1, 2, 3, 4, 5, 6 and 8 h) after administration, the concentrations of plantamajoside in plasma were measured and the main pharmacokinetic parameters were estimated. The study indicates that the pharmacokinetics of plantamajoside in rat plasma have significant differences between two groups.